ඵලදායී කෘෂිකාර්මික පිළිවෙත් හරහා සෞඛ්‍යාරක්ෂිතව සහ තිරසාරව එළවළු වගා කරන්නේ කෙසේද? - International Water Management Institute (International Water Management Institute, 2024)
How to grow vegetables, safely and sustainably, through effective agricultural practices in Sri Lanka?